Creating and sustaining arts-based school reform [ the A+ schools program - Noblit, George W. (Routledge, 2009)
An analysis of arts in education initiatives, based on the A+ School Program. This book discusses the political,fiscal, and curricular implications inherent in taking the arts seriously and offers a